SYNERGIZING CRISPR-CAS9 GENE EDITING WITH PHARMACOLOGICAL INTERVENTIONS: EMERGING PARADIGMS IN GENETIC DISORDER THERAPEUTICS (The Research of Medical Science Review, 2025)
The combination of CRISPR-based gene editing and pharmacological therapies offers a promising strategy for treating genetic diseases. CRISPR enables precise genome modifications (base/prime editing, knock-in/out), while advanced delivery systems enhance its therapeutic potential. In cancer immunotherapy, CRISPR-engineered CAR-T cells address challenges like autologous production, drug resistance, and toxicity. Combining CRISPR with drugs improves efficacy, overcomes resistance, and optimizes delivery by targeting DNA repair pathways. However, challenges such as off-target effects, immune responses, and ethical concerns remain. Pharmacological agents can boost CRISPR precision by inhibiting DNA repair. Future efforts should refine CRISPR systems, integrate AI-driven personalized medicine, and tackle polygenic diseases. Rigorous research, ethical oversight, and regulatory frameworks are essential before clinical adoption. While progress is encouraging, further improvements in safety, efficacy, and accessibility are needed to establish this approach as a mainstream therapy.